Arabic-Java Writing System: How Javanese Language Adopts Arabic Script - Fakron Jamalin; Asma Abdul Rahman (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
Borrowing script happens throughout history of languages. Long before we know Latin script, Javanese has already adopted Arabic script. However, Java language deals with problematic adaptation due to distinctive sound system among those two languages, Arabic and Java. For that matter, this research aims to uncover 1) how Arabic-Java orthography represents Javanese’s consonants and vowel, and 2) how Arabic-Java orthography represents Javanese’s cluster. This research uses qualitative descriptive method. Data contain with the Javanese words which is written in Arabic script. Data are gained from eight different books which are inscribed by Arabic-Java orthography. After data are collected, the orthography method and grapheme-phoneme correspondence are used to analyze them. Grapheme-phoneme correspondence used to know how Arabic-Java orthography represents consonants and vocal phonemes. Finally, this research found that Arabic-Java orthography has 28 graphemes which are used to represent 23 consonants. Modification letters and digraph are used to represent missing sound in Arabic. Six Javanese vocals are represented with 9 graphemes. In another hand, cluster is written in two ways, first by adding Anaptyxis schwa [ə] in between sonorant-sonorant or obstruent-sonorant and vowel [a] in initial cluster nasal consonant and plosive consonant.